2007
DOI: 10.1017/s0007114507243077
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence of information from single frequency v. bioimpedance spectroscopy in bodybuilders

Abstract: In bioelectrical impedance spectroscopy (BIS), it is assumed that the current path is only extracellular at the lowest frequencies and that it is both extra-and intracellular at the highest frequencies. We tested validity of BIS assumptions in bodybuilders who have an increased intracellular volume due to hypertrophy of muscle fibres. The study was observational cross-sectional in a study group of thirty professional bodybuilders compared with thirty control subjects. Resistance (R) and reactance (Xc) vector c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
43
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 31 publications
6
43
1
Order By: Relevance
“…Body composition was assessed using bioelectrical impedance analysis (BIA Akern Bioresearch, Pontassieve, FI, Italy) which is a non-invasive and portable method for the estimation of fluid compartments, fat and fat-free mass in healthy subjects. Bioelectrical impedance analysis was chosen for the analysis of body composition due to its reliability, safety, convenience and non-invasiveness making it optimal for the routine monitoring of body composition during the ketogenic diet [25,26]. The experimental design is showed in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Body composition was assessed using bioelectrical impedance analysis (BIA Akern Bioresearch, Pontassieve, FI, Italy) which is a non-invasive and portable method for the estimation of fluid compartments, fat and fat-free mass in healthy subjects. Bioelectrical impedance analysis was chosen for the analysis of body composition due to its reliability, safety, convenience and non-invasiveness making it optimal for the routine monitoring of body composition during the ketogenic diet [25,26]. The experimental design is showed in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the potential health-related implications, PhA has been investigated as a means to assess nutritional status (Zhang et al, 2014). In the areas of exercise science and sports medicine, PhA has often been analyzed in cross-sectional observational (Piccoli et al, 2007) and prospective (Mascherini et al, 2015;Matias et al, 2015) studies. Cross-sectional studies have shown that the PhA can be affected by physical activity (Dittmar, 2003;Torres et al, 2008;Koury et al, 2014;Mala et al, 2015).…”
mentioning
confidence: 99%
“…In fact, studies had shown that using BCS equations in MHD patients could achieve physiological fluid status and better control of hypertension [26,27]. However, it was found that the BISA used in DW BCS did not provide any improvement over single-frequency measurement at 50 kHz for the estimation of hydration status [28,29]. The equivalence of information from single versus multifrequency bioimpedance was due to tissue anisotropy.…”
Section: Discussionmentioning
confidence: 99%